2020
DOI: 10.1371/journal.pcbi.1008450
|View full text |Cite
|
Sign up to set email alerts
|

In silico mutagenesis of human ACE2 with S protein and translational efficiency explain SARS-CoV-2 infectivity in different species

Abstract: The coronavirus disease COVID-19 constitutes the most severe pandemic of the last decades having caused more than 1 million deaths worldwide. The SARS-CoV-2 virus recognizes the angiotensin converting enzyme 2 (ACE2) on the surface of human cells through its spike protein. It has been reported that the coronavirus can mildly infect cats, and ferrets, and perhaps dogs while not pigs, mice, chicken and ducks. Differences in viral infectivity among different species or individuals could be due to amino acid diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 51 publications
0
29
0
Order By: Relevance
“…There are also arguments to exonerate the pangolin from SARS-CoV-2 transmission to humans ( Andersen et al, 2020 ; Frutos et al, 2020a ). In silico investigations on ACE2 polymorphism indicated that the list of SARS-CoV-2 susceptible species includes M. javanica (pangolin), Macaca mulatta (monkey), Felis catus (cat), Canis lupus (dog), Oryctolagus cuniculus (rabbit), Mustela putorius furo (ferret), Mesocricetus auratus (hamster), Bos taurus (cow), Bubalus bubalus (buffalo), Capra hircus (goat), Ovis aries (sheep) but not Mus musculus (mouse) ( Blanco et al, 2020 ; Damas et al, 2020 ; Lam S. D. et al, 2020 ; Luan et al, 2020a , b ; Qiu et al, 2020 ; Devaux et al, 2021 ). This result is a strong argument in favor of the “circulation model” in which there is no particular intermediate host but a circulation of viruses among many susceptible species including humans with no visible epizootic ( Frutos et al, 2020b , 2021b ).…”
Section: Introductionmentioning
confidence: 99%
“…There are also arguments to exonerate the pangolin from SARS-CoV-2 transmission to humans ( Andersen et al, 2020 ; Frutos et al, 2020a ). In silico investigations on ACE2 polymorphism indicated that the list of SARS-CoV-2 susceptible species includes M. javanica (pangolin), Macaca mulatta (monkey), Felis catus (cat), Canis lupus (dog), Oryctolagus cuniculus (rabbit), Mustela putorius furo (ferret), Mesocricetus auratus (hamster), Bos taurus (cow), Bubalus bubalus (buffalo), Capra hircus (goat), Ovis aries (sheep) but not Mus musculus (mouse) ( Blanco et al, 2020 ; Damas et al, 2020 ; Lam S. D. et al, 2020 ; Luan et al, 2020a , b ; Qiu et al, 2020 ; Devaux et al, 2021 ). This result is a strong argument in favor of the “circulation model” in which there is no particular intermediate host but a circulation of viruses among many susceptible species including humans with no visible epizootic ( Frutos et al, 2020b , 2021b ).…”
Section: Introductionmentioning
confidence: 99%
“…The RBD/hACE2 interaction structures represent the domains of both proteins that contribute to this interaction, providing the basis for computational protein-protein interaction studies, mutation analysis, drug design and computational models of the full spike protein, as it is harder to maintain a similar resolution for significantly larger structures [ 38 , 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, in all structures focusing on this interaction in wild-type SARS-CoV-2 S protein, the contact interface is divided into two clusters at both ends of the α1 helix in hACE2, leaving a central cavity filled with water [ 40 , 43 ]. In these sections, there are over 10 H-bonds, multiple salt bridges, π-stacking and non-polar interactions [ 36 , 40 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The binding of the spike protein to the host ACE2 receptor is the first and one of the most important steps in SARS-CoV-2 infection of host cells. While the history of early adaptation is unknown, the RBD of the SARS-CoV-2 spike protein appears to be highly specialized to human ACE2 [72]. Substitution of eight SARS-CoV-2 RBD residues proximal to the ACE2-binding surface with those found in RaTG13 is almost universally detrimental to human ACE2 receptor usage [73].…”
Section: Discussionmentioning
confidence: 99%